Strategie w systemie zarządzania antykryzysowego - Krzakiewicz, Kazimierz; Cyfert, Szymon (Strategies in Anticrisis Management System, 2008)
The aim of this article is to discuss the idea of strategies in anticrisis management system. The article starts with a description of an idea of anticrisis management. This helps to present strategies of anticrisis management and to discuss the pace of accomplishment of anticrisis change.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 163-170